The Role of Brand Equity, Service Quality, and Organizational Commitment as Mediators of Lecturer Performance: A Study at the University of Muhammadiyah Makassar - Hisnol Jamali; Asriati Asriati; Syarifuddin Arief (Al-Buhuts, 2024)
This study examines the impact of brand equity, service quality, and organizational commitment on lecturer performance through lecturer work loyalty at the University of Muhammadiyah Makassar. Using a descriptive quantitative research approach, data was collected from 106 respondents through questionnaires. Hypothesis testing was conducted using Path Analysis and Sobel Test methods. The findings indicate that while brand equity has a positive but nonsignificant effect on work loyalty, service quality and organizational commitment significantly influence work loyalty. Furthermore, brand equity, service quality, organizational commitment, and lecturer work loyalty have a positive and significant effect on lecturer performance. However, brand equity does not significantly influence lecturer performance through work loyalty, whereas service quality and organizational commitment do so significantly. The study concludes that improvements in brand equity, service quality, and organizational commitment positively impact increased work loyalty and lecturer performance. Institutions of education can enhance the quality of education they provide by improving lecturer performance and strengthening the relationship between lecturers, students, and the institution. This can be achieved through deeper measurement of brand equity, cross-cultural analysis, the development of integrative models and lecturer development programs, as well as the implementation of marketing strategies.